THE MERITS OF QUIZLET FOR VOCABULARY LEARNING AT TERTIARY LEVEL - Agung Ginanjar Anjaniputra; Vina Aini Salsabila (Indonesian EFL Journal, 2018)
Vocabulary has been at the pinnacle of language learning since vocabulary mastery helps in communicating language. However, learning vocabulary yields problems prevalent among learners of this new digital era such as low participation and difficulties to keep learners attentive to lessons being learned. Deploying classroom action research, this study aims to depict the implementation of Quizlet in learning vocabulary at the tertiary level and to elicit learners' responses to Quizlet utilization in the classroom. In this regard, observation and interview were triangulated to get an enhanced portrayal of what occurred during the learning. These instruments resulted in findings that Quizlet to some extent helped in fostering learners’ engagement, as well as persistence in vocabulary learning and that the learners enjoyed learning vocabulary in Quizlet and considered Quizlet as useful and beneficial tool for their learning development, particularly in vocabulary learning. Hence, it is suggested that teachers make use of Quizlet to provide learners with a new way of learning that is interesting, innovative, and probably improving learners’ learning experiences, eventually fulfilling the learners’ demand of the 21st century.Keywords: Vocabulary learning; Quizlet; learner engagement; CALL